Expression of Mosquito MicroRNA Aae-miR-2940-5p Is Downregulated in Response to West Nile Virus Infection To Restrict Viral Replication - Slonchak, Andrii (American Society for Microbiology, 2014)
West Nile virus (WNV) is an enveloped virus with a single-stranded positive-sense RNA genome from the Flaviviridae family. WNV is spread by mosquitoes and able to infect humans, causing encephalitis and meningitis that can be fatal; it therefore presents a significant risk for human health. In insects, innate response to RNA virus infection mostly relies on RNA interference and JAK/SAT pathways; however, some evidence indicates that it can also involve microRNAs (miRNAs). miRNAs are small noncoding RNAs that regulate gene expression at posttranscriptional level and play an important role in a number of processes, including immunity and antiviral response. In this study, we focus on the miRNA-mediated response to WNV in mosquito cells. We demonstrate that in response to WNV infection the expression of a mosquito-specific miRNA, aae-miR-2940, is selectively downregulated in Aedes albopictus cells. This miRNA is known to upregulate the metalloprotease m41 FtsH gene, which we have also shown to be required for efficient WNV replication. Correspondingly, downregulation of aae-miR-2940 reduced the metalloprotease level and restricted WNV replication. Thus, we have identified a novel miRNA-dependent mechanism of antiviral response to WNV in mosquitoes. IMPORTANCE A detailed understanding of vector-pathogen interactions is essential to address the problems posed by vector-borne diseases. Host and viral miRNAs play an important role in regulating expression of viral and host genes involved in endogenous processes, including antiviral response. There has been no evidence to date for the role of mosquito miRNAs in response to flaviviruses. In this study, we show that downregulation of aae-miR-2940 in mosquito cells acts as a potential antiviral mechanism in the mosquito host to inhibit WNV replication by repressing the expression of the metalloprotease m41 FtsH gene, which is required for efficient WNV replication. This is the first identification of an miRNA-dependent antiviral mechanism in mosquitoes, which inhibits replication of WNV. Our findings should facilitate identification of targets in the mosquito genome that can be utilized to suppress vector population and/or limit WNV replication.